Moisture absorption characteristics of natural fiber composite sandwich structures in a hygrothermal environment - Nicholas Kuan, Hoo Tien; Mohamad Zaki, Mohd Amin; M. Y. M, Zuhri (CRC PRESS. Taylor & Francis Group, 2025)
A sandwich structure could be an enticing structural choice for aerospace, automotive, and vessel applications as far as it could remain sensitive to climatic change. However, these structures continue to be vulnerable to moisture uptake when compared to composite laminates and significantly reduce the structural performance. Hence, the goal of this chapter is to explore the current topic of the influence of water absorption on biobased composite sandwich structures. In this chapter, sample preparations are initially presented. Then, a simple model that is used to evaluate the water absorption characteristics of biobased sandwich structures is described. It consists of equilibrium moisture uptake, Fickian, Langmuir, and time-variable diffusion models. In general, the mechanical properties of conditioned samples were assessed concerning their dry counterparts. The results indicated that water immersion exposure significantly reduced the structural performance. In conjunction with standard approaches to understanding moisture behavior, finite-element analysis (FEA) is also widely explored. It is hypothesised that the robust mechanical performance and good environmental endurance of sandwich composites provide a synergistic effect with several benefits in terms of eco-friendliness and structural design for use as moisture-resistant systems in a wide range of applications.